The Quest for Today's Totemic Psychology: A New Look at Wundt, Freud and Other Scientists. (12th June 2018) - Lee, Yueh-Ting; Chen, Xiangyang; Zhao, Yongping; Chen, Wenting
Abstract : Totems are symbols or representations of human's affiliations with, and/or categorizations of, animals, plants and inanimate objects. Totemism is related to fundamental human belief systems based on totems. Investigating totems and totemism psychologically is a unique way to explore human minds. We have critically examined Wundt, Freud and many other scholars and scientists who made distinguished contributions to scientific research on totems and totemism almost in the past two centuries –i.e., totemic psychology, which is the study of our mind's categorization and affiliation in the human and natural world today. Understanding and appreciating their totemic psychology can help psychologists today enhance their understanding in other fields—e.g., ecological and environmental psychology, biological psychology, cognitive psychology, personality, social and ethnic psychology, clinical and counseling psychology, cultural psychology, and religious or spiritual psychology. Unfortunately, recent data from a content analysis via PsycInfo and a cross-cultural survey study ( N =273) showed that well-trained psychologists around the world and psychology students in the United States and in China are unfamiliar with Wundt and Freud's totemic contributions to psychology today. The implications, benefits, and lessons of totems and today's totemic psychology are discussed here.